Recent Development in the Presentation of Earnings Per Share. - Harwell, Jeff L.; Nichols, III, William S.; Steffler, Scott D. (The Accounting Review, 1974)
This article focuses on how a constantly evolving procedure in the field of accounting is the presentation, calculation, and meaning of earnings per share (EPS). This evolution has caused most textbook material to become quickly dated and incomplete. The purpose of this article is to present a short example for classroom use that illustrates the current reporting requirements for the presentation of earnings per share data. The reporting of earnings per share on all outstanding shares of common stock has been a practice of many firms for many years. Traditionally, the EPS figure was included only as supplemental information in annual reports. However, this practice has undergone rapid evolution in recent years. In 1966, in its Opinion Number 9, the Accounting Principles Board (APB) strongly recommended that earnings per share data be presented on the face of the income statement. APB Opinion Number 15, issued in May 1969, changed this recommendation to a requirement, thus bringing EPS under the scope of the auditor's report.